TRADITIONAL GAMES AS ONE OF THE ALTERNATIVE LEARNING MODELS IN SHAPING CHILDREN'S CHARACTERS - Hendrowati, Tri Yuni (STMIK Pringsewu, 2021)
This research is to find out how traditional games as one of the alternative learning models in shaping the character of children in SD Negeri 2 Sendangasih. This type of descriptive research with a qualitative approach. Instruments used include illustrated storybooks, dolls, counterfeit items, plants, drawings. And the most commonly used is to use storybook props. This research is a class action research, conducted through three cycles each cycle consisting of preparation, implementation, observation, and interview. Judging from the results of the research that has been done shows a sufficient improvement The results of the study show: (1) The process of character building in the classroom, family, and community through traditional children's games at SD Negeri 2 Sendangasih, the process of character education is carried out by balancing between moral knowing, moral feeling, and moral action. The habit of using moral knowing, moral feeling, and moral action on every decision will educate people to be human beings with character, who have clear principles and handles. (2) Character values that develop in the classroom, family, and community at SD Negeri 2 Sendangasih include values related to the creator, values related to oneself, values related to others, values related to the environment, and national values. (3) The impact of character education planting through traditional games at SD Negeri 2 Sendangasih includes children becoming more creative, socially high, confident, more harmonious with family, manners, socializing well, and the output has a positive impact.